From Participatory Culture to Participatory Fatigue: The Problem With the Public. (July 2019) - Porlezza, Colin
The Web has changed newswork dramatically. After the turn of the Millennium, the Web 2.0 was welcomed as a unique medium of participation, interaction, and democratization. Due to the increased interactivity of many websites, and the growing prominence of social networking sites such as Facebook that invited the creation and publication of user contributions, many journalism scholars promulgated the potentials of the Web to trigger participation, a new interactivity and, eventually, more transparency, accountability, and responsiveness. In this article, I show how I was equally full of hope that the participatory potential of the Web would become widespread among news organizations. However, recent findings show that most established newsrooms still do not practice what they preach. Even more so, many newsrooms show a participation fatigue, closing user comment sections due to participation inequality or challenging phenomena such as trolls, incivility, or hate-speech. Hence, I do not believe that the majority of legacy news media will further implement accountability practices and strengthen their responsiveness toward their publics. But I still have hope, and this hope comes from entrepreneurial journalism.